2023
DOI: 10.7150/ijbs.81939
|View full text |Cite
|
Sign up to set email alerts
|

Novel Implication of the Basement Membrane for Breast Cancer Outcome and Immune Infiltration

Abstract: Therapeutic failure in breast cancer patients is largely attributed to postoperative advancement and therapy resistance. Nevertheless, an efficacious prognostic signature for recognizing this population is lacking. The basement membrane (BM) has been proven to be strongly involved in cancer progression and metastasis, and has the potential to be a powerful predictor in breast cancer. In this study, substantial bulk RNA transcriptomics, single cell RNA transcriptomics and clinical information were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, the ROC and calibration curves of the external validation cohort further confirmed the significant predictive value of our model (Figure 2 G, H). Taken together, these results demonstrated the outstanding performance of our nomogram compared with previously established prognostic models 43 - 45 .…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In addition, the ROC and calibration curves of the external validation cohort further confirmed the significant predictive value of our model (Figure 2 G, H). Taken together, these results demonstrated the outstanding performance of our nomogram compared with previously established prognostic models 43 - 45 .…”
Section: Resultssupporting
confidence: 68%
“…Recently, several models have been developed to predict the prognosis of BC patients. Tian et al have built a prognostic model using basement membrane-related genes 43 . Cui et al have also established a nomogram based on nicotinamide metabolism-related signature 44 , while Li's model was constructed utilizing m6A-related genes 45 .…”
Section: Discussionmentioning
confidence: 99%
“…BMGs may be predominantly expressed in stromal cells, particularly in cells involved in the production and maintenance of the basement membrane, such as fibroblasts and myoepithelial cells. These cells synthesize and secrete matrix components, forming the structure of the basement membrane [ 7 , 8 ]. However, Laminin-511 has been implicated in cell migration, tumor growth, and metastasis, with higher levels of this isoform found in many breast, lung, thyroid, and prostate cancers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recent studies have reported that basement membranes interact with the immune microenvironment to promote tumor progression. [12] As of now, prognostic features related to the basement membrane have been established with high predictive accuracy in liver cancer, [13] breast cancer, [14] and lung adenocarcinoma. [15] However, research in this area regarding gastric cancer (GC) is limited.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, prognostic features related to the basement membrane have been established with high predictive accuracy in liver cancer, [ 13 ] breast cancer, [ 14 ] and lung adenocarcinoma. [ 15 ] However, research in this area regarding gastric cancer (GC) is limited.…”
Section: Introductionmentioning
confidence: 99%